Comparing Tinnitus Tuning Curves and Psychoacoustic Tuning Curves - Fournier, Philippe (Trends Hear, 2019)
Tinnitus masking patterns have long been known to differ from those used for masking external sound. In the present study, we compared the shape of tinnitus tuning curves (TTCs) to psychophysical tuning curves (PTCs), the latter using as a target, an external sound that mimics the tinnitus characteristics. A secondary goal was to compare sound levels required to mask tinnitus to those required to mask tinnitus-mimicking sounds. The TTC, PTC, audiometric thresholds, tinnitus pitch, and level matching results of 32 tinnitus patients were analyzed. Narrowband noise maskers were used for both PTC and TTC procedures. Patients were categorized into three groups based on a combination of individual PTC–TTC results. Our findings indicate that in 41% of cases, the PTC was sharp (V shape), but the TTC showed a flat configuration, suggesting that the tinnitus-related activity in that subgroup does not behave as a regular stimulus-induced activity. In 30% of cases, V-shape PTC and TTC were found, indicating that the tinnitus-related activity may share common properties with stimulus-induced activity. For a masker centered at the tinnitus frequency, the tinnitus was more difficult to mask than the mimicking tone in 72% of patients; this was particularly true for the subset with V-shape PTCs and flat TTCs. These results may have implications for subtyping tinnitus and acoustic therapies, in particular those targeting the tinnitus frequency.